2020
DOI: 10.1186/s12968-020-00610-6
|View full text |Cite
|
Sign up to set email alerts
|

Standardized image interpretation and post-processing in cardiovascular magnetic resonance - 2020 update

Abstract: With mounting data on its accuracy and prognostic value, cardiovascular magnetic resonance (CMR) is becoming an increasingly important diagnostic tool with growing utility in clinical routine. Given its versatility and wide range of quantitative parameters, however, agreement on specific standards for the interpretation and post-processing of CMR studies is required to ensure consistent quality and reproducibility of CMR reports. This document addresses this need by providing consensus recommendations develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
189
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 569 publications
(215 citation statements)
references
References 89 publications
(98 reference statements)
2
189
0
12
Order By: Relevance
“…In rare cases, patient-specific frequency adjustment may be required. 4. Devices that have been tested and determined to be safe at 1.5 T may not be safe at 3 T. Please check specific information relating to CMR safety of devices at higher magnetic field strengths.…”
Section: Field Strength Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In rare cases, patient-specific frequency adjustment may be required. 4. Devices that have been tested and determined to be safe at 1.5 T may not be safe at 3 T. Please check specific information relating to CMR safety of devices at higher magnetic field strengths.…”
Section: Field Strength Considerationsmentioning
confidence: 99%
“…The second task force will be updating the document on Reporting published by that SCMR Task Force in 2010 [3]. The 3rd task force will be updating the 2013 document on Post-Processing [4]. All protocols relative to congenital heart disease are covered in a separate document [5].…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion criteria were as follows: (1) Patients were previously con rmed to have SARS-CoV-2 infection, (2) patients were recovered from COVID-19 and discharged from the hospital for 12 weeks, (3) patients agreed to participate in the study and signed informed consent. The exclusion criteria were as follows: (1) Patients has undergone pacemaker surgery, (2) patients with uncontrolled high blood pressure, (3) patients with coronary heart disease (evidence of coronary artery stenosis > 50%) or previous myocardial infarction, (4) patients with moderate to severe valvular dysfunction, (5) patients with previous atrial brillation, (6) previous heart failure, (7) previous myocarditis, (8) patients with known cardiomyopathy, (9) patients with severe renal insu ciency (creatinine clearance rate < 30 mL/min/1.73 m 2 , (9) patients who cannot cooperate with breath-holding and cannot undergo CMR examination, (10) pregnant women, (11) patients are not suitable as clinical subjects due to other factors.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Cardiovascular magnetic resonance imaging (CMRI) can visualize and quantify heart volume and function and characterize the myocardial tissue; thus, it has been used as a gold standard non-invasive imaging tool in cardiovascular medicine 10 . A recent single-center study from Wuhan demonstrated that more than half of the recovered COVID-19 patients sustain cardiac edema, brosis, and impaired right ventricle (RV) contractile function 11 .…”
Section: Introductionmentioning
confidence: 99%
“…22 As outlined in Table 4, cMRI will be used to evaluate myocardial function and structure. cMRI was selected over other imaging modalities, such as cardiac CT and echocardiography, because it enables accurate, highresolution assessment of myocardial injury (e.g., fibrosis, inflammation, edema) [23][24][25] , is considered to be more reproducible for measuring LV function and volumes 26,27 , and does not require additional radiation exposure. In addition, cMRI enables assessment of myocardial strain, which may have greater sensitivity than LVEF in predicting clinical outcome 28 , particularly in chemotherapy-induced cardiomyopathy 29 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%